P191 CONTEMPORARY CHARACTERISTICS AND OUTCOMES OF PATIENTS WITH NON–ST ELEVATION MYOCARDIAL INFARCTION ACCORDING TO MANAGEMENT STRATEGIES. (18th May 2022) - Orso, F; Casolo, G; Szasz, C; Forni, S; D'Arienzo, S; Gemmi, F
Abstract: Purpose: The aim of the present study was to analyze, in a large administrative database, the clinical characteristics and prognosis of a contemporary population of patients with Non–ST elevation myocardial infarction (NSTEMI) according to the treatment strategy. Methods: This retrospective observational study included patients residing in the Tuscany region, aged 18+ years, discharged from a regional hospital with a diagnosis of NSTEMI (main diagnosis ICD–9–CM codes 410.7 or 411.1 in HDA) between 2016 and 2018. Patients were classified into two main groups: a conservative strategy (CON) group and an invasive strategy (INV) group that was further classified into three subgroups: a PCI group, a CABG group, and a group where patients were managed invasively but not revascularized. Results: The study population consisted of 15, 208 patients. The median age was 76 ± 9 years, females were 38.5%. Groups composition according to management strategies is shown in Figure 1 . Compared to INV patients, patients in the CON group were older (mean age 85 vs 72 years, p < 0.0001), more frequently female (54% vs 33%, p < 0.0001), had a higher cardiovascular and non–cardiovascular comorbidity burden. All–cause mortality rates in hospital and 1–year MACCE (Figure 2 and 3 ) were 3% and 24.1%, resulting significantly higher in the CON strategic management group than in the INV strategic group: 8.9% vs 1.1; 34.0 vs 21.1%; p = 0.0001. Between the three INV subgroups we found no differences in hospital mortality, while at 1 year there was a significant difference in MACCE with a higher rate in the CABG group compared to the PCI subgroups and in that of invasively managed but not revascularized patients: CABG: 42.8% vs 19.3% vs 18.2% respectively, p = 0.0001 Conclusions: Real–world data show that patients with NSTEMI have significantly different characteristics and prognosis according to treatment strategy. Patients managed non–invasively have more complex characteristics and worse prognosis both in the hospital and after discharge. Patients who have been managed invasively but treated with medical therapy represent an interesting subgroup worthy of further study.